2019
DOI: 10.1038/s41467-019-08487-5
|View full text |Cite
|
Sign up to set email alerts
|

A cell cycle-coordinated Polymerase II transcription compartment encompasses gene expression before global genome activation

Abstract: Most metazoan embryos commence development with rapid, transcriptionally silent cell divisions, with genome activation delayed until the mid-blastula transition (MBT). However, a set of genes escapes global repression and gets activated before MBT. Here we describe the formation and the spatio-temporal dynamics of a pair of distinct transcription compartments, which encompasses the earliest gene expression in zebrafish. 4D imaging of pri-miR430 and zinc-finger-gene activities by a novel, native transcription i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 68 publications
4
74
0
Order By: Relevance
“…1c; Supplementary movie 2). In good agreement with previous reports (Chan et al, 2018;Hadzhiev et al, 2019), RNAP2 Ser2ph foci were co-localized with bright miR-430 Morpholino signals in living embryos, suggesting that the nuclear and local concentration of RNAP2 Ser2ph-Fab reports on transcription activity in living zebrafish embryos, even though the sensitivity may not be as high as the transcript-specific Morpholino, which binds stably to the target RNA compared to the transient binding of Fabs.…”
Section: Monitoring Zgasupporting
confidence: 92%
See 2 more Smart Citations
“…1c; Supplementary movie 2). In good agreement with previous reports (Chan et al, 2018;Hadzhiev et al, 2019), RNAP2 Ser2ph foci were co-localized with bright miR-430 Morpholino signals in living embryos, suggesting that the nuclear and local concentration of RNAP2 Ser2ph-Fab reports on transcription activity in living zebrafish embryos, even though the sensitivity may not be as high as the transcript-specific Morpholino, which binds stably to the target RNA compared to the transient binding of Fabs.…”
Section: Monitoring Zgasupporting
confidence: 92%
“…miR-430 family genes that play a role for clearance of maternal RNAs are expressed at the highest level among the early transcribed genes (Hadzhiev et al, 2019;Heyn et al, 2014). To confirm this notion, a Cy3-labeled Morpholino oligonucleotide that targets miR-430 transcripts (Hadzhiev et al, 2019) was injected with Alexa488-labeled RNAP2 Ser2ph-Fab into living embryos ( Fig. 1c; Supplementary movie 2).…”
Section: Monitoring Zgamentioning
confidence: 86%
See 1 more Smart Citation
“…We find that the mir-430 cluster, which is transcribed two orders of magnitude higher than any other region, undergoes a dramatic loss in accessibility when elongation of RNA polymerase II is blocked. The miR-430 cluster is one of the first to be transcribed and initially, all transcribing RNA polymerase II localizes to the two alleles of the miR-430 cluster [19][20][21]56], which might facilitate the formation of RNA-pol II 'trains' capable of evicting nucleosomes, as shown in vitro [33].…”
Section: Locusmentioning
confidence: 98%
“…1995; Hadzhiev et al, 2019;Müller et al, 2001). In Drosophila and zebrafish, it has been observed that the majority of the early transcripts are short and lack introns, leading to the suggestion that the early interphases simply are not long enough to sustain robust transcription of most genes (McKnight and Miller, 1976;Shermoen and O'Farrell, 1991;Rothe et al, 1992;De Renzis et al, 2007;Chen et al, 2013;Heyn et al, 2014;Kwasnieski et al, 2019).…”
mentioning
confidence: 99%